The occurrence of immune-related adverse events is an independent risk factor both for serum HBsAg increase and HBV reactivation in HBsAg-positive cancer patients receiving PD-1 inhibitor combinational therapy - Zeng, Yingfu; Huang, Jiwei; Pang, Jiahui; Pan, Shufang; Wu, Yuankai; Jie, Yusheng; Li, Xinhua; Chong, Yutian (Frontiers in Immunology, 2024)
Previous studies have indicated the potential of PD-1/PD-L1 inhibitors in the treatment of chronic HBV infection. However, since phase Ⅲ clinical trials have not yet been announced, more information may be obtained if we observe the changes in serum HBsAg and HBV-DNA levels in cancer patients receiving PD-1 inhibitors. We aimed to explore the impact of PD-1 inhibitor combinational therapy on serum HBsAg and HBV-DNA levels and investigate the incidence of HBsAg loss, HBV reactivation (HBVr), and immune-related adverse events (irAEs). Then, identifying the risk factors associated with significant HBsAg fluctuations and HBVr. Therefore, a retrospective study including 1195 HBsAg-positive cancer patients who received PD-1 inhibitors between July 2019 and June 2023 was undertaken, and 180 patients were eligible for final analysis.Comparisons of serum HBsAg levels after PD-1 inhibitor initiation were made between groups. The Pearson χ 2 or Fisher exact test was performed to investigate the relationships between categorical variables. Univariable and multivariable analysis were performed to identify the risk factors for significant HBsAg fluctuations and HBVr. Our study showed that with concurrent use of antiviral agents, serum HBsAg levels decreased (P < 0.0001) in 129 patients and increased (P=0.043) in 51 patients, with 7 patients (3.89%) achieved HBsAg loss. Virus replication was suppressed in most of the enrolled patients. When divided patients into different subgroups, significant HBsAg decreases after PD-1 inhibitor exposure were discovered in lower baseline HBsAg group (P=0.023), HBeAg-seronegative group (P=0.028), non-irAEs occurrence group (P=0.045) and liver cancer group (P=0.047). Of note, 11 patients and 36 patients experienced HBVr (6.11%) and irAEs (20%), respectively, which could lead to discontinuation or delayed use of PD-1 inhibitors. After multivariable analysis, HBeAg-seropositive (P=0.01) and irAEs occurrence (P=0.02) were identified as independent risk factors for significant HBsAg increase, irAEs occurrence (P=0.01) was identified as the only independent risk factor for HBVr. In brief, our study showed PD-1 inhibitors combined with nucleos(t)ide analogues (NAs) may exert therapeutic potential for chronic HBV infection in cancer patients, attention also should be paid to the risk of significant HBsAg increase, HBVr, and irAEs in PD-1 inhibitor combinational therapies.